The Role of Innovation in Business Planning: Creating Competitive Advantage through Creative Strategy - Abdullah As Shoib; Agung Winarno (CAKRAWALA : Management Science Journal, 2025)
The success of business is the main goal for companies, especially in the face of increasingly fierce competition in the global market. The dynamics of market changes, technological developments, and changing consumer preferences force companies to continue to innovate and adapt. This research aims to understand the role of innovation in business planning and how creative strategies based on innovation can be used to create competitive advantage. Using a literature study approach, this research highlights how innovation is not only important in developing new products but also in creating more effective and efficient business strategies. Innovation-based creative strategies enable companies to respond to market challenges in a more flexible way, introduce solutions that differentiate the company from its competitors, and create significant added value for customers. The results of this study show that the integration of innovation in business planning and innovation-based creative strategies is a major factor in creating sustainable competitive advantage. The findings provide useful practical and theoretical insights for companies, academics, and policy makers in formulating more adaptive and future-oriented business strategies.